Effect of biogenic polyamines on sliding motility of mycobacteria in the presence of antibiotics - I. V. Tsyganov; A. G. Tkachenko (Вавиловский журнал генетики и селекции)
Nowadays, sliding is the least investigated mode of bacterial motility. Sliding is a process of passive movement on the surface of semi-liquid mediums which was originally described for mycobacteria and other bacterial species deprived of the organelles specialized for movement. Some mycobacteria are able to colonize surfaces, including tissues of macro-organisms, using glycopeptidolipids localized in the cell envelope for this aim. This is a serious problem for effective therapy of mycobacteriosis caused by nontuberculosis mycobacteria. Furthermore, animal tissues contain biogenic polyamines, which can increase tolerance of microorganisms to stresses, including antibiotics, and modulate cell motility. Therefore, studying mutual effects of biogenic polyamines and antibiotics on the expansion of mycobacteria is important for medicine. Mycobacterial strains, including the parent Mycolicibacterium smegmatis mc2 155 and strains containing single (ΔrelMsm) or double (ΔrelMsmΔrelZ) deletions, were used as the objects of this study. The content of glycopeptidolipids was determined using thin layer chromatography. Sliding motility was assessed by measuring the area of the sliding colony. The effectiveness of antibiotics was measured by comparison of the areas of sliding colonies in the presence of comparable concentrations of antibiotics. The polyamines spermidine and spermine had different effects on the sliding of mycobacteria through an increase or decrease in the colony areas. At the same time, polyamines had neither bactericidal nor bacteriostatic effects. The polyamines contained in the medium decreased the bactericidal effects of the antibiotics streptomycin or isoniazid, but enhanced the effects of DMNP, a synthetic analogue of the natural antibiotic erogorgiaene. Rifampicin was the most effective of all antibiotics investigated here. Moreover, we found that glycopeptidolipids are, apparently, not the only regulators of mycobacterial sliding.